Analisis Yuridis terhadap Dugaan Pelanggaran Hukum Lingkungan dalam Kasus Pemasangan Pagar Laut di Tangerang dan Implikasinya terhadap Penegakan Hukum Pesisir di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The installation of sea fences in Tangerang has triggered significant environmental law violations, affecting coastal ecosystems and the lives of local communities. This study aims to analyze the legal aspects of these violations and their impacts on coastal law enforcement in Indonesia. Using qualitative descriptive methods, data were collected through observation and in-depth interviews with various stakeholders. The results of the study indicate that the installation of the fences was carried out without permits and environmental impact analysis (AMDAL), and resulted in decreased fish catches and loss of community access to marine space. Weak law enforcement and minimal community participation in decision-making exacerbate these problems. This study contributes to the understanding of the importance of integration policies, legal awareness, and the need for active community participation in coastal resource management. The implications of the research results underline the urgent need to improve collaboration between stakeholders and strengthen law enforcement for environmental sustainability. Suggestions for further research include investigating similar violations in other coastal areas in Indonesia.